National security and the menace of the nipah virus, 1998 – 2000: The Malaysian experience - Wan Nur Izzati Wan Bahari,; Ahmad Kamal Ariffin Mohd Rus,; Zulkanain Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In 1998, Malaysian mainly pig farming community was bombarded with the tragedy of a new infectious disease. The emergence of this new virus in the world has dealt a major blow to Malaysia. The superficiality of understanding the Nipah Virus has disrupted public well-being. Simultaneously, the frailty caused by the spread of infectious disease has changed the perspective of how national security is viewed. Thereby, the national security defence no longer focuses on the demarcation aspect of the area alone, but also involves every individual living in the supposed area. Thus, this article examines the menace of the Nipah virus outbreak posed on national security between 1998 and 2000. The Nipah virus was first recognized in Malaysia. The Government as the main actor had no comprehensive plan when faced with this new disease. While the main requirement needed in overcoming epidemics requires sustainable prevention. This article uses historical methodology, which emphasizes on qualitative method in the form of descriptive analytics. Primary and secondary sources was used throughout the process of data accumulation, for instance Guidelines of Nipah Infection MOH/K/EPI/19.99(GU), parliament hansard, periodicals, books and articles. The findings show the Nipah outbreak managed to threaten national security, however the capability of the Nipah epidemic to achieve this threat was not solely dependent on high mortality rates, but on other aspects as well, such as, economic disruption and public panic. Government preparedness in health infrastructure, through declaring infectious zones, biosecurity steps, disinfections, and public awareness campaigns yielded effective results in controlling the Nipah outbreak.